Pleozymes: Pleiotropic Oxidized Carbon Nanozymes Enhance Cellular Metabolic Flexibility - Anh T. T. Vo; Karthik Mouli; Anton V. Liopo; Philip Lorenzi; Lin Tan; Bo Wei; Sara A. Martinez; Emily A. McHugh; James M. Tour; Uffaf Khan; Paul J. Derry; Thomas A. Kent (Nanomaterials)
Our group has synthesized a pleiotropic synthetic nanozyme redox mediator we term a “pleozyme” that displays multiple enzymatic characteristics, including acting as a superoxide dismutase mimetic, oxidizing NADH to NAD+, and oxidizing H2S to polysulfides and thiosulfate. Benefits have been seen in acute and chronic neurological disease models. The molecule is sourced from coconut-derived activated charcoal that has undergone harsh oxidization with fuming nitric acid, which alters the structure and chemical characteristics, yielding 3–8 nm discs with broad redox potential. Prior work showed pleozymes localize to mitochondria and increase oxidative phosphorylation and glycolysis. Here, we measured cellular NAD+ and NADH levels after pleozyme treatment and observed increased total cellular NADH levels but not total NAD+ levels. A 13C-glucose metabolic flux analysis suggested pleozymes stimulate the generation of pyruvate and lactate glycolytically and from the tricarboxylic acid (TCA) cycle, pointing to malate decarboxylation. Analysis of intracellular fatty acid abundances suggests pleozymes increased fatty acid β-oxidation, with a concomitant increase in succinyl- and acetyl-CoA. Pleozymes increased total ATP, potentially via flexible enhancement of NAD+-dependent catabolic pathways such as glycolysis, fatty acid β-oxidation, and metabolic flux through the TCA cycle. These effects may be favorable for pathologies that compromise metabolism such as brain injury.